The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4236/ojped.2021.113049
|View full text |Cite
|
Sign up to set email alerts
|

Does Caffeine Citrate Administration Decrease Risk of Acute Kidney Injury in Hospitalized Preterm Neonates?

Abstract: Background: Acute kidney injury (AKI) is a life threatening condition with still high mortality rate in neonates. Early recognition of the risk factors and the rapid effective treatment of the contributing conditions will reduce AKI in the neonatal period. Aim of the Work: To determine association between early caffeine citrate administration and risk of acute kidney injury in hospitalized preterm neonates. Patients and Methods: This study was a prospective study that was conducted at the NICU of El Galaa Teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Four similarly constructed prospective cohort studies have been conducted in neonates of various prematurity to ascertain differences in AKI rates between caffeine- and non-caffeine-exposed babies [ 55 , 56 , 57 , 58 ]. All studies included 100 neonates each and found that neonates given caffeine had lower prevalences of AKI.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four similarly constructed prospective cohort studies have been conducted in neonates of various prematurity to ascertain differences in AKI rates between caffeine- and non-caffeine-exposed babies [ 55 , 56 , 57 , 58 ]. All studies included 100 neonates each and found that neonates given caffeine had lower prevalences of AKI.…”
Section: Resultsmentioning
confidence: 99%
“…All studies included 100 neonates each and found that neonates given caffeine had lower prevalences of AKI. All four also noted lower peak SCr levels in caffeine-exposed neonates; three reached statistical significance [ 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations